Self-talk and competitive balance beam performance - Van Dyke, E. D.; Van Raalte, J. L.; Mullin, E. M.; Brewer, B. W. (The Sport Psychologist, 2018)
Little research has explored the relationship between highly skilled athletes` self-talk and their competitive performance over the course of a season. For the current study, positive, negative, motivational, instructional, and functional dimensions of collegiate gymnasts` (N?=?141) self-talk were assessed. The gymnasts` competitive balance beam performances in intercollegiate meets were also recorded. Multiple regression analysis revealed that positive self-talk significantly predicted balance beam performance and performance consistency. Significant positive correlations were found among key self-talk variables, except negative self-talk. Significant negative correlations were found between negative self-talk and self-talk functions (i.e., attention, cognitive and emotional control, and confidence). The results highlight the interrelationships among various types and functions of self-talk in competitive settings, and provide evidence for the ways in which self-talk is related to the performance of highly skilled athletes. Suggestions for how these findings might be applied by athletes, coaches, and sport psychology practitioners are provided.